A qualitative study on the motivations to bariatric surgery of patients with obesity (肥胖症患者寻求减重手术动机的质性研究) - XU Mengyu (徐梦瑜); LIANG Xiaoyu (梁晓宇); SUN Longhao (孙龙昊); HU Fang (胡芳); ZHANG Yan (张妍) (中西医结合护理)
Objective To understand the feelings and to explore the motivations of domestic obese people undergoing bariatric surgery. Methods Phenomenological research design and semi-structural interviews were conducted on 15 obesity patients who undergoing bariatric surgery, and the collected data were analyzed with the method of Colaizzi Phenomenological analysis. Results By analyzing and sorting out the data, 5 themes related to the motivation of pursuing bariatric surgery were put forward: improving health and longevity; treating obesity-related complications; improving quality of life; improving appearance, self-image and social interaction, and controlling poor eating behavior. Conclusion Improving health and prolonging life, treating obesity-related diseases and optimizing quality of life are the biggest reasons for obesity patients to seek bariatric surgery. When giving patients the choice of obesity treatment and outcome education, these factors should be taken into account, which will help to individualization encourage obese patients to better accept bariatric surgery. (目的 了解国内肥胖人群进行减重手术的心理感受, 探索国内肥胖症患者寻求减重手术的动机。方法 对15名进行减重手术的肥胖症患者进行半结构访谈, 并用质性研究中的Colaizzi现象学研究方法整理、分析资料。结果 通过分析和整理资料提炼出减重手术动机相关的5个主题: 改善健康和寿命; 治疗肥胖相关合并症; 提高生活质量; 改善外表、自我形象和社会互动以及控制不良饮食行为。结论 改善健康延长寿命、治疗肥胖相关疾病和优化生活质量是促使肥胖症患者寻求减重手术的最主要的原因。当对患者进行肥胖症治疗方案选择和结果教育时, 医护人员应考虑上述因素, 个性化激励国内肥胖人群更好地接受减重手术。)